2006
DOI: 10.13182/fst06-a1231
|View full text |Cite
|
Sign up to set email alerts
|

Significance of MHD Effects in Stellarator Confinement

Abstract: Substantial progress has been achieved to raise the plasma beta in stellarators and helical systems by high power neutral beam heating, approaching reactor relevant values [1][2][3]. The achievement of high-β operation is closely linked with configuration effects on the confinement and with magnetohydrodynamic (MHD) stability. However, the observed pressure gradients indicate some mitigation of the effects on the plasma confinement, presumably because of the high collisionality of high-β plasmas and island hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 58 publications
2
43
0
Order By: Relevance
“…Configurations were studied, Figure (6), that covered a wide range of aspect ratios, from 3 to 8, for a given rotational transform and β = 4%. These configurations possess good quasi-axisymmetry and are also MHD stable to the external kinks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Configurations were studied, Figure (6), that covered a wide range of aspect ratios, from 3 to 8, for a given rotational transform and β = 4%. These configurations possess good quasi-axisymmetry and are also MHD stable to the external kinks.…”
Section: Discussionmentioning
confidence: 99%
“…Figure (7) shows the shape of flux surfaces for A = 8 at toroidal angles corresponding to the beginning of a field period and at the half-period. For A = 8 and β = 4%, the Tryon (6). Coil winding surfaces have been constructed such that the inboard midplane is displaced by 0.6a whereas the outboard miplane is displaced by 1.2a, where a is the plasma minor radius, with interpolation made for locations in between.…”
Section: Configurations With the Increasing Aspect Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…4,[7][8][9] For diverted tokamaks, there has been some success in suppressing edge localized modes (ELMs) by the imposition of nonaxisymmetric fields near the plasma edge, 10 and the possible role of the stochastic layer produced near the diverter separatrix is a subject of current research. Additionally, it has recently been shown that the observed electron thermal conductivity in one type of discharge in the National Spherical Torus Experiment is in quantitative agreement with a theory of transport due to magnetic-field-line stochasticity produced by magnetic perturbations from microtearing instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Only in recent years have stellarators achieved values of β sufficiently high to study the issue experimentally. Both the W7AS and LHD stellarators exhibit degraded confinement at high values of β that does not appear to be caused by instabilities, [7,8] There is no diagnostic in these experiments that directly indicates whether surfaces are broken. In this paper we compare experimental observations on the W7AS stellarator with PIES code calculations to investigate this issue.…”
Section: Introductionmentioning
confidence: 99%